Ideal Weight and Weight Discrepancy: A Study of Life Course Trajectories and Intercohort Change in the Netherlands - Liliya Leopold; Liliya Leopold (Frontiers Media S.A., 2024)
Objective: This study examined how individuals' ideal weight and weight discrepancy (between ideal and actual weight) changed over the life course and across cohorts.Methods: The study used population-representative longitudinal data collected in the Netherlands (N = 61,431 observations between 2007 and 2018 among N = 13,409 individuals aged 16 to 80 and born 1927-2000).Results: Ideal weight increased linearly with age. Weight discrepancy showed a bell-shaped age pattern. Approximately half of the age-related increase in ideal weight was associated with concurrent increases in actual weight. Ideal weight and weight discrepancy increased slightly across cohorts. The cohort-related increase in ideal weight vanished after adjusting for change in actual weight. Analyses of population heterogeneity showed similar patterns of change in both outcomes across groups, although levels differed by gender, education, and migration status even after adjusting for differences in actual weight between these groups.Conclusion: These results show that ideal weight and weight discrepancy in the Netherlands change substantially with age and modestly across cohorts. Potential explanations include changes in physical appearance and in the importance of physical appearance.